Molecular marker-based detection of Ph1b mutation to increase homoeologous pairing in wheat (Triticum aestivum) - SINGH, RAJENDER; TYAGI, BHUDEV SINGH; PAHWA, GEETA; SAREEN, SINDHU; TIWARI, RATAN (The Indian Journal of Agricultural Sciences, 2012)
Despite the close relationship between three genomes of wheat, meiosis in wheat is characterized by formation of bivalents only. The homologous pairing of polyploidy wheat is controlled by Ph1 (pairing homologous) locus located on long arm of chromosome 5B which suppresses pairing and recombination between homoeologous chromosomes. However, similar genes have also been identified in T. turgidum and T. timopheevii with lesser impact. Cytogenetic manipulations for suppressing the Ph1 pairing regulation would be necessary to bring about the desired chromosome pairing and hence alien gene transfers into cultivated wheat. In the present study, PCR based marker was used to transfer the recessive mutation in Ph1 locus (Ph1b) from bread wheat cultivar Chinese Spring to Indian bread and durum wheat cultivars. The availability of Ph1b locus in Indian wheat genetic background will help in transfer of alien genes of economic and agronomic importance.